Interstrand Crosslinking Involving Guanine: A New Major UVC Laser‐Induced Biphotonic Oxidatively Generated DNA Damage. (22nd January 2022) - Angelov, Dimitar; Lone, Imtiaz Nisar; Menoni, Hervé; Cadet, Jean
ABSTRACT: Several classes of oxidatively generated DNA damage including oxidized purine and pyrimidine bases, interstrand base crosslinks and DNA‐protein crosslinks have been previously shown to be generated in both isolated DNA and cellular DNA upon exposure to either 266‐nm laser irradiation or one‐electron oxidants. In this study, we provide evidence that biphotonic ionization of guanine bases by UVC laser irradiation of double‐stranded deoxyoligonucleotides in aerated aqueous solutions induces the formation of interstrand crosslinks (ICLs). This is supported by various experiments including sequencing gel analyses of formed photoproducts and effects of UVC laser intensity on their formation. This constitutes a novel example of the diversity of reactions of guanine radical cation that can be generated by various one‐electron oxidants including UVC laser biphotonic ionization, direct effect of ionization radiation and type I photosensitizers. However, the exact structure of the interstrand base adducts that is a challenging analytical issue remains to be further established. Examples of relevant biochemical/structural applications of biphotonic induction of ICLs in DNA samples by high‐intensity UVC laser pulses are provided. Abstract : Exposure of double stranded DNA to a single high‐intensity 266 nm nanosecond laser pulse generates interstrand crosslinks by biphotonic ionization mechanisms and hole trapping by guanines. This novel guanine‐specific lesion is highly sensitive to temperature or protein induced conformational changes and can be used as a sensor of local DNA base pair opening.